The UAE Federal Legislator’s Contemporary Criminal Policy Against Adultery Crimes: An Analytical Study - Dganni, Khald (Journal of Legal Sciences, 2023)
In this research, we addressed the modern criminal policy of the UAE legislator in the face of adultery, in accordance with the most recent amendments under Decree No. 31 of 2021 on crimes and penalties, in which the federal legislator adopted a modern criminal policy in an attempt to balance the protection of the public freedom of individuals, including sexual freedom, with the protection of family ties, by criminalizing the adultery of the husband or wife or those under the mandate to describe the position of the female with her consent under the text of article 409 of the aforementioned law. The male, and what confirms to us this is the adoption of the narrow concept of the position, so that the site is limited to the natural penetration of the penis of the man in the female vagina, in addition to that in article 409/1 of the Crimes and Penalties Act has specified to us the sex of the perpetrator in this crime, so that it is male to female, which assures us that the federal legislator adopts the narrow concept achieved by the crime of adultery, as stipulated by the federal legislator for the crimes of female or sodomy to mention a presumed element For the conduct of the crime, which is consent to unlawful sexual intercourse by the female or male, and in the absence of it, we are a crime signed under duress, in addition to the element of consent, the federal legislator has set the age of 18 to express consent unlike some other legislation that raised the age of expression of consent at the age of 21. The federal legislator also went to the primacy of the private interest over the public interest in society to punish the crime of female positioning with consent, by suspending the movement of criminal proceedings against the complaint of the husband or the guardian, as well as the UAE legislator in criminalizing between the husband or wife, where the crime, which is the position of the female with her consent, whether the husband is caught in the position of a female with her consent in the matrimonial home or outside, and therefore the federal legislator came out of the criticism that was directed to legislation that required the establishment of a crime that required the establishment of a crime The husband adultered the woman and her husband in adultery in the matrimonial home, and well the federal legislator did what he went to.